Caracterización del turista que visita el cantón Pedernales para el planteamiento de estrategias de diversificación de productos turísticos - Mera Bravo, Eliana Pilar (2019)
The purpose of this research is to characterize the tourist for the planning of diversification strategies for tourist products in the Pedernales canton. This research was carried out in two fundamental phases: the first one consisted of the identification of the tourist profile, which was possible with the gathering of information carried out through the design of a data collection tool with which a survey directed at 381 was applied. people. The profile of the client raised revealed that mostly tourists are internal, framed between 20 and 40 years and come mainly from the province itself and the Sierra region. They are primarily personnel employed in public institutions, motivated by beaches and gastronomy and consider Pedernales as a safe place with high satisfaction. The second phase took into consideration the Georeferencing of the study area, a description of natural and cultural elements and characteristics existing in the Pedernales destination; in order to arrive at the approach of diversification strategies. The proposals made focus on the constitution of a Tourist Observatory, the establishment of collaboration schemes with the academic and business sectors, the design and promotion of this destination in a more inclusive, technological, responsible way with the environment, ecosystems and resources . Finally, there is a strengthening of the regulatory framework for regulatory improvement and tourism facilitation, around the competitiveness of the sector in Pedernales.